Pruning automatic sphere decoding algorithm and performance analysis - LI Ying; WEI Ji-bo (Tongxin xuebao)
A pruning automatic sphere decoding（PASD） algorithm was presented to reduce the complexity and keep the efficiency of ASD simultaneously.The proposed algorithm efficiently reduced the size of the border node list in ASD by statistical pruning,and obtained the tradeoff between the performance of symbol error ratio（SER） and complexity by setting reasonable parameter’s values.Analysis and simulation show that for a higher level（more than 4） modulation,PASD is able to reduce the number of comparisons by at least 30% as compared to ASD without much penalty of the performance in the same SNR region.